Densa tessitura: uma leitura em contraponto, a visão da academia sobre a produção literária de Marina Colasanti - Miguel, Maria Aparecida de Fátima [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Although Marina Colasanti (1937) is considered by the critics as one of the exponents of Brazilian children and youthful literature, and having her production, in this segment, published since the outset 1980s until this moment, still is very unsystematic the study of literary criticism on the writer's work. This work takes as object a significant sample of academic production about the literary production of the writer, leaning on dissertations and on theses that analyze the Children's and the youthful work of Marina Colasanti, as those that turn to literary texts that have been priority addressed to adult readers, considering that, sometimes, these two literary universes are shown merged. Twenty academic papers constitute the corpus of this work, it has been identified through the database Capes and the query at physical and virtual libraries of various universities. From a methodological point of view, the corpus received a homogeneous treatment for data collection, have been subjected to a grid (or "chart") compose of 15 different categories that guided the study of each thesis or dissertation. That systematic analysis propitiated, as research results, concludes in a kind of balance on the critical fortune, being possible sight four main topics that concern to the critical studies on the work of Marina Colasanti, according to different theoretical perspectives: the female specific; the myth; the poetic language; and the love.

Embora Marina Colasanti (1937) seja considerada pela crítica especializada como um dos expoentes da literatura infantojuvenil brasileira, tendo sua produção nesse segmento sido publicada desde o início da década de 1980 até o momento presente, ainda é bastante assistemático o estudo da fortuna crítica sobre a obra da escritora. O presente trabalho toma por objeto uma amostra significativa da produção acadêmica sobre a produção literária da escritora, debruçando-se tanto sobre dissertações e teses que analisam a obra infantojuvenil de Marina Colasanti quanto aquelas que se voltam aos textos literários que têm sido endereçados prioritariamente aos leitores adultos, considerando-se que, por vezes, esses dois universos literários se apresentam mesclados. Vinte trabalhos acadêmicos constituem o corpus deste trabalho, tendo sido identificado por meio do Banco de Dados da Capes e da consulta a bibliotecas físicas e virtuais de diversas Universidades. Do ponto de vista metodológico, o corpus recebeu um tratamento homogêneo para a coleta de dados, tendo sido submetido a uma grade (ou “tabela”) composta por 15 diferentes categorias que orientaram o estudo de cada tese ou dissertação. Essa análise sistemática propiciou que, como resultado da pesquisa, se tenha chegado a uma espécie de balanço sobre a fortuna crítica, em que é possível divisar quatro principais tópicos de que se ocupam os estudos críticos sobre a obra de Marina Colasanti, segundo diferentes perspectivas teóricas: o específico feminino; o mito; a linguagem poética; e o amor.
Dense tessitura: reading in counterpoint , a vision academy of the literary production Marina Colasanti
Keywords: Children's literature; Youthful literature; Children and youthful literature; Contemporary Brazilian literature; Critical fortune; Marina Colasanti; Literatura infantil; Literatura juvenil; Literatura infantojuvenil; Literatura brasileira contemporânea; Fortuna crítica